'Isolated base‐of‐slope aprons': An oxymoron for shallow‐marine fan‐shaped, temperate‐water, carbonate bodies along the south‐east Salento escarpment (Pleistocene, Apulia, southern Italy). Issue 1 (10th October 2021) - Tropeano, Marcello; Spalluto, Luigi; Meloni, Demetrio; Moretti, Massimo; Sabato, Luisa
Abstract: This paper regards the lower Pleistocene temperate‐water carbonate deposits disconformably overlying an escarpment made up of faulted Cretaceous to Miocene limestones of the Apulia Foreland (southern Italy). Study deposits discontinuously crop out along the present‐day eastern Salento sea cliff, and form isolated fan‐shaped bodies, up to 1 km wide and up to 40 to 50 m thick, each of them covering an area of a few square kilometres. The internal arrangement of beds is represented by up to 25° to 30° lobate, seaward dipping clinobeds thinning and onlapping onto a rocky foreslope in the proximal sector and passing to gently inclined to sub‐horizontal strata in the distal sector. Seven facies were distinguished, mainly composed of coarse‐grained skeletal carbonates made up of a heterozoan association including coralline algae, large and small benthic foraminifera, echinoids, molluscs, bryozoans and serpulids. Since clinobeds were formed thanks to hyperconcentrated density flows (grain flows) bypassing the upper part of the inherited escarpment, these skeletal grains represent ex situ deposits whose shallow‐marine factory was located upward (landward) with respect to the bypassed zone, likely in the almost flat area on top of the Salento Peninsula. Clinobeds are often affected by tens of metres wide and long channel‐like structures interpreted as landslide scars. Inside these gullies, contorted beds (slumps) or matrix‐supported intra‐bioclastic floatstone/rudstone (massive deposits) are present. The occurrence of supercritical‐flow structures (for example, backset‐bedded beds) indicates the development of hydraulic jumps along the steep slope of gullies. Since these clinostratified, fan‐shaped carbonate bodies represent carbonate slopes, and that the latter are known as aprons, normally related to linear sourced sediments, an acceptable oxymoron for studied fan‐shaped carbonate bodies is suggested: 'isolated base‐of‐slope aprons'.